ANALYSIS OF COGNITIVE BARRIERS IN CHILDREN'S UNDERSTANDING OF MATHEMATICS LEARNING CONCEPTS - Nurfazyelah, Nurfazyelah; Imani, Cahya; Hidayah, Nurul; Mutahara, Nurul; Safitri, Ana; Abira, Abrar (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the cognitive obstacles experienced by elementary school students in understanding mathematical concepts. Cognitive obstacles refer to difficulties that arise from students’ limited thinking processes in connecting abstract mathematical ideas with their concrete experiences. Through a case study conducted by reviewing various educational and cognitive psychology literature, it was found that factors such as low logical reasoning ability, insufficient understanding of basic concepts, and the use of less varied instructional methods are the primary causes of students’ cognitive barriers. In addition, low learning motivation and the limited use of interactive learning media further intensify students’ difficulties in comprehending mathematical concepts. Efforts that teachers can undertake include implementing contextual learning strategies, using concrete learning media, providing individual guidance, and fostering reflective thinking in order that students can construct their conceptual understanding independently. Therefore, this analysis is expected to provide meaningful contributions to the development of more effective mathematics learning approaches in elementary schools.